Accepting Evolution Entails Kufr ?: A Critical Appraisal of Nuh Ha Mim Keller’s Fatwa - Shoaib Ahmed Malik; Elvira Kulieva; Ayub Ayub (UIN Sunan Kalijaga Yogyakarta, 2021)
Muslim scholars who oppose the compatibility of Islam and evolution usually advance three kinds of arguments: scientific, metaphysic, and hermeneutic. This paper will examine the position of Nuh Ha Mim Keller, a prominent Sunni scholar who employ these three lines of arguments and proposes that believing in human evolution entails kufr. In this article we will critically analyze Keller’s understanding of the science of evolution in which he claims that the theory of evolution is not robust. We argue that through the consilience of induction, evolution is the best explanation for the biological origins and diversity. We also argue that a more nuanced understanding of the metaphysical and hermeneutical aspects of Islam and evolution debate would reveal that Keller’s anti-evolution claims are unwarranted, including his accusation of kufr against those who accept human evolution.